Prevention of Corruption in Local Self-Government Bodies: Legal Regulation And Foreign Experience - Anton Borysenko; Halyna Tatarenko; Oksana Brusakova; Alla Pyshna; Nataliia Bilak (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
The article focuses on the negative impact of corruption on the efficiency of the state, the reduction of the governability of the state, and the deterioration of the organization of public life even in the conditions of war in Ukraine. Prevention of corruption risks in local self-government bodies should be implemented by authorities exclusively at the level of a legislative act, necessarily in compliance with the principle of the rule of law and the corresponding guarantees of security in a certain state. The article analyzes in detail the legislation of Ukraine (administrative and criminal legal frameworks) regarding the prevention of corruption risks in local self-government bodies. It was concluded that the strengthening of responsibility for corruption in the conditions of martial law in Ukraine is fully justified, as it is aimed at preventing the "reduction" of international aid during the war and striking preventive strikes by equating corruption with collaboration with the enemy. A scientific vision of the legislative approach to solving the problem of combating corruption in Ukraine is formulated, taking into account the realistic goals of such activities and the war in the country. It has been proven that prevention of corruption risks in local self-government bodies is possible with the help of the following measures: anti-corruption mechanisms at the legislative level and in the activities of public administration bodies; formation of an effective system of state institutions that actually implement state policy in the field of combating corruption risks; prosecution of natural persons for corruption in the form of deprivation of liberty and other measures; intolerance of the population to corruption in war conditions. Attention is focused on the need for states to comply with international standards, namely the recommendations of GRECO and the Istanbul Action Plan of the OECD Anti-Corruption Network.